2011
DOI: 10.1167/iovs.10-6826
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone, a Peroxisome Proliferator–Activated Receptor-γ Agonist, Induces Dilation of Isolated Porcine Retinal Arterioles: Role of Nitric Oxide and Potassium Channels

Abstract: Pioglitazone elicits endothelium-dependent and -independent dilation of retinal arterioles mediated by NO release and Kv channel activation, respectively. The NO-mediated dilation pathway probably occurs via activation of guanylyl cyclase, PI3-kinase/Akt, and AMPK signaling. Understanding the effect of pioglitazone on retinal vasculature may provide new insights into therapeutic advances for treating diabetic retinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…8,9,11,21,22,35,36 The current data showed that the BK Ca channel blocker, iberiotoxin, inhibited cilostazol-induced vasodilation (Fig. 3) in the same manner as the nonselective K channel blocker, TEA, whereas this vasodilation was unaffected by glibenclamide, suggesting that the BK Ca channel, which can produce membrane hyperpolarization that results in relaxation of smooth muscle, 37 may be involved primarily in cilostazol-induced vasodilation of the retinal arterioles.…”
Section: Figurementioning
confidence: 63%
See 3 more Smart Citations
“…8,9,11,21,22,35,36 The current data showed that the BK Ca channel blocker, iberiotoxin, inhibited cilostazol-induced vasodilation (Fig. 3) in the same manner as the nonselective K channel blocker, TEA, whereas this vasodilation was unaffected by glibenclamide, suggesting that the BK Ca channel, which can produce membrane hyperpolarization that results in relaxation of smooth muscle, 37 may be involved primarily in cilostazol-induced vasodilation of the retinal arterioles.…”
Section: Figurementioning
confidence: 63%
“…11 Briefly, the vessel was perfused intraluminally with a nonionic detergent, CHAPS (0.4%), for 1 to 2 minutes to remove the endothelial cells, 10,13 which we confirmed previously by immunohistochemical staining. 11 …”
Section: Endothelial Denudationmentioning
confidence: 84%
See 2 more Smart Citations
“…[27][28][29][30] Briefly, the isolated retinal arterioles (90-110 lm in situ) were cannulated with a pair of glass micropipettes and pressurized to 55 cm H 2 O intraluminal pressure without flow by using two independent pressure reservoir systems. 31 The internal diameter of the isolated vessels was recorded continuously by using videomicroscopic techniques throughout the experiments.…”
Section: Isolation and Cannulation Of Microvesselsmentioning
confidence: 99%